The judge as an indirect victim in criminal proceedings and their possible impediment to adjudicate: an analysis of Impediment Claim No. 165 of the Federal Supreme Cort of Brazil - e Silva Neta, Elenita Araújo (Ius Humani. Jornal do direito, 2025)
Recently, in Brazil, there has been constant questioning as to whether Justice Alexandre de Moraes, as a judge, could act in Petition No. 12 100, which is being processed before the Supreme Federal Court (STF). This case involves the possible crimes committed by former President Jair Bolsonaro and his colleagues in relation to an attempted coup d'état in 2022. In this context, the question covered in the article is the following: is it possible for the judge, as an indirect victim of a crime, to judge the case, or would he be prevented from doing so according to article 252, paragraph IV, of the Code of Criminal Procedure (CCP)? The objective of the article is to examine whether the judge, as an indirect victim, becomes directly interested in the resolution of the case or becomes a party to it, which would prevent him from judging it. To prepare the article, the deductive method and qualitative research were used, as well as some references from the main scholars who address the topic, such as Nucci (2014), Ferrajoli (2002) and Campos (2024).